2021
DOI: 10.1002/agg2.20171
|View full text |Cite
|
Sign up to set email alerts
|

Potential amendments for improving productivity of low carbon semiarid soil

Abstract: Applying soil amendments with high C content can potentially improve soil properties and increase crop yields. The objective of this 3-yr field study was to evaluate the effects of organic amendments on soil organic C (SOC), chemical properties, crop nutrient uptake, and crop yields in a low C sandy loam soil near Scottsbluff, NE. The field was planted to dry bean (Phaseolus vulgaris L.) in 2017, maize (Zea mays L.) in 2018, and sugar beet (Beta vulgaris L.) in 2019. Char at 22.3, 44.6, 66.9, 89.2, and 133.8 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…In addition, adding char to agricultural soil along with chemical fertilizer or manure can provide other ecosystem service benefits such as SOC accumulation and soil health improvements. Maharjan, Panday et al (2021) reported an enhanced corn yield in a low C soil (7 g C kg −1 ; exposed subsoil) with char applied at >6.5 Mg C ha −1 . This suggests that C-deficient soils of water-limited regions may benefit more from soil amendments such as char or manure as they can increase soil water retention and nutrient cycling and supply (Blanco-Canqui et al, 2020;Panday et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adding char to agricultural soil along with chemical fertilizer or manure can provide other ecosystem service benefits such as SOC accumulation and soil health improvements. Maharjan, Panday et al (2021) reported an enhanced corn yield in a low C soil (7 g C kg −1 ; exposed subsoil) with char applied at >6.5 Mg C ha −1 . This suggests that C-deficient soils of water-limited regions may benefit more from soil amendments such as char or manure as they can increase soil water retention and nutrient cycling and supply (Blanco-Canqui et al, 2020;Panday et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This report underscores the significance of separating the application timing of organic amendments and herbicides and the benefit of incorporating amendments to avert herbicide absorption impacting their performance. Maharjan et al (2021) reported that the lower the original soil C level, the more significant and faster the CCR effect on soil properties and crop yield. The soil C in this experiment was 10.1 g kg −1 , but the yield benefit of CCR application was observed only in a few cases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Maharjan et al. (2021) reported improved maize yield in a dry bean–maize–sugar beet rotation with CCR applied at >6.5 Mg C ha −1 on exposed sub‐soil with C of 7 g C kg −1 , indicating that CCR amendments might have more pronounced benefits in soils with lower C content compared to those with higher C content. This underlines the significance of soil type in influencing the effects of CCR on crop yield, with low C‐content soils potentially benefiting from CCR due to enhanced soil water retention and nutrient availability (Blanco‐Canqui et al., 2020; Panday et al., 2021).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…During the coal pyrolysis procedure, volatile substances are released in gas and tar, accounting for up to 70% weight loss in the coal, and the remaining material (char) is porous activated carbon [21,22]. Heavy metal-containing soil amendments applied to farmlands can have harmful short-term or long-term effects on the wellbeing of people [23,24]. However, the CC and BC used in this study have very low concentrations of trace elements, which are far below the permissible levels in soil.…”
Section: Introductionmentioning
confidence: 99%